Tuberculous meningitis as a complication of sarcoidosis. Issue 6 (June 1974) - Hopkins, Anthony
Abstract : In two patients with well established sarcoidosis, the acute onset of meningitis proved to be due to tuberculosis rather than to an extension of sarcoid granulomata to the meninges. The cerebrospinal fluid changes are very similar, and the differential diagnosis rests on a search for Mycobacterium tuberculosis.